2022
DOI: 10.1002/cjce.24389
|View full text |Cite
|
Sign up to set email alerts
|

DEM simulations of spherical particle–particle collisions

Abstract: The randomness, diversity, and complexity of the high‐speed particle crushing process bring great difficulties to the theoretical analysis of powder engineering. In this paper, the discrete element method is used to simulate the collision of spherical particles, which provides a reference for studying the process and mechanism of crushing between particles under impact load. The Hertz–Mindlin with bonded contact model is used as the particle–particle contact model. The central collisions of particles with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Comprehensive simulations have shown that the proposed approach can lead to significant improvements of more than 20% in soil moisture estimation. [ 2 ]…”
mentioning
confidence: 99%
“…Comprehensive simulations have shown that the proposed approach can lead to significant improvements of more than 20% in soil moisture estimation. [ 2 ]…”
mentioning
confidence: 99%